WASH, nutrition and health-seeking behavior during COVID-19 lockdowns: Evidence from rural Bangladesh - van Gurp, Margo; Riad, Imam M.; Islam, Kazal A.; Islam, Md Shariful; Geervliet, Remco M.; Bakker, Mirjam I. (PLOS ONE, 2022)
A general lockdown to minimize to slow transmission of COVID-19 in Bangladesh came into effect on March 26th and lasted until May 30th. The lockdown had far-reaching economic implications for the population, with many facing economic hardship due to loss of income. Despite the attempt of the government to ease economic hardship by means of social safety net packages, people suffered from poor access to health services, and financial and food insecurity. This is likely to have disastrous consequences for the nutritional status of young children. This cross-sectional study measured the impact of the first general lockdown on food consumption of young children, access to water, handwashing and health seeking behavior, and the ability to maintain livelihood among households with children under the age of 5, in rural Bangladesh. The result of the analysis suggest that loss of income was reported by almost all respondents across all socio-economic groups. However, the poorest households were less likely to provide for sufficient food for their families and had to reduce consumption of food. Diet diversity and food intake–particularly animal protein sources—for young children were severely affected. On the other, increased awareness of handwashing and access to soap were also reported. The pandemic is likely to be detrimental to the nutritional status of children in Bangladesh and can exacerbate existing health inequities. Strong social safety net programs are needed to protect vulnerable populations to consequences of restrictive measures, supported in design and implementation by non-governmental organizations.